Endoscopic Transorbital Approach to Middle Cranial Fossa and Kawase's Triangle—Feasibility, Descriptive and Quantitative Anatomical Study - Mehta, Sarthak; Srinivas, Dwarakanath; Singh, Gyani Jail; Deora, Harsh; Mahadevan, Anita (Journal of Neurological Surgery Part B: Skull Base, 2025)
Skull base surgeries have increasingly adopted minimally invasive endoscopic transnasal approaches; however, limitations such as restricted accessibility to lesions located lateral to the optic nerve and internal carotid artery have led to exploring alternative routes like the orbit for accessing the middle cranial fossae. This study investigates transorbital endoscopic approaches in cadavers, focusing on the middle cranial fossa's anatomy and evaluating the potential and challenges of exposing the middle skull base and petrous apex.To assess the surgical anatomy and feasibility of anterior petrosectomy via a transorbital endoscopic approach, provide essential morphometric data, and evaluate associated morbidity through a systematic literature review.Using a 0-degree Karl Storz Endoscope 10 sides of five cryopreserved cadavers were dissected through a lateral retrocanthal incision. Step-by-step photographs of anterior petrosectomy through the endoscopic transorbital route are taken, and evaluation of access to middle fossa triangles is performed. A systematic PubMed review analyzed 47 studies (in vivo and anatomical dissections) regarding the transorbital approach's indications, techniques, and complications.In cadavers with a 50-cm head circumference, the median distances from the conjunctival incision to the superior orbital fissure (SOF) and inferior orbital fissure (IOF) lateral borders were 1.8 and 1.9 cm, respectively. The median length of the petrous bone drilled was 2.0 cm. Additional measurements of intracranial landmarks were recorded.The study confirmed the feasibility of using a transorbital endoscope to explore the middle cranial fossa base through a lateral retrocanthal incision, offering improved visualization. However, caution is necessary due to the proximity of intra-orbital structures.
Keywords: endoscopic; transorbital; Kawase's triangle; petrous apex; cavernous sinus